Synthesis, assembly, and electrochromic properties of uniform crystalline WO3 nanorods - Wang, Jinmin (2012)
We report the synthesis of uniform crystalline WO3 nanorods and their assembly without any surfactants. WO3 nanorods have been synthesized by using a facile hydrothermal process without employing lithium ions and sulfates. Transparent WO3 nanorod film has been prepared by assembled coating of the as-synthesized WO3 nanorods suspension onto ITO coated glass. It is found that the assembly was not affected by the surface properties of substrates, but dependent on the drying rate of the film, the concentration of suspension, and the aspect ratio of nanorods. The assembly process is proposed to follow an aggregation−deposition mechanism. The resulting WO3 nanorod film exhibits high electrochromic stability and comparable color display, contrast, and coloration/bleaching response.